Acute hepatitis at the Department of Pediatrics, School of Medicine, University of North Sumatera/Dr. Pirngadi Hospital, Medan - Mahadi Mahadi; Syahril Pasaribu; Munar Lubis; Chairuddin P. Lubis (Paediatrica Indonesiana, 1991)
Pirngadi Hospital revealing 41 cases of acute hepatitis, consisted of 61.0% boys and 39.0% girls. The majority of patients were below five years of age (68.3%). There were 37.1% cases with malnutrition. The common symptoms were fever, jaundice, vomiting and dark urine. On laboratory examination there were 10 cases with positive HBs Ag. Accompanying diseases were malnutrition, bronchopneumonia, anemia, bronchitis and pulmonary tuberculosis. A total of 63.4% oj patients were healed, 29.3% discharged against medical advice and 7.3 % died because of bronchopneumonia and hepatic coma.